Study on Security and Privacy in Healthcare Data Mining - E. Kesavulu Reddy (Issues and Development in Health Research Vol. 6, 2021)
Managing the privacy and security of healthcare information used to mine data by reviewing its fundamentals, components, and principles, as well as applicable laws and regulations. It also includes a literature review on technical issues in privacy assurance, as well as a case study demonstrating some potential pitfalls in data mining of personally identifiable information. Data mining especially when it draws information from multiple sources poses special problems. This paper provided recommendations for medical data miners regarding privacy and security best practises.